Stereotypes about people living with HIV: implications for perceptions of HIV risk and testing frequency among at-risk populations. - Earnshaw, Valerie A; Smith, Laramie R; Chaudoir, Stephenie R; Lee, I-Ching; Copenhaver, Michael M (AIDS education and prevention : official publication of the International Society for AIDS Education, 2012)
Although research continues to demonstrate that HIV stigma is associated with decreased HIV testing, the psychological processes implicated in this association remain unclear. The authors address this gap by differentiating between the HIV stigma mechanisms of stereotypes, prejudice, and discrimination. They hypothesize that HIV stereotypes specifically, more so than prejudice or discrimination, are associated with HIV testing among at-risk populations. Ninety-three HIV-negative people receiving methadone maintenance therapy at a clinic in the northeastern United States participated by completing a survey. Results demonstrated that HIV stereotypes are associated with HIV testing via the mediator of perceived HIV risk. As hypothesized, prejudice, discrimination, and objective HIV risk were not associated with perceived HIV risk. Differentiating between HIV stigma mechanisms in future work can provide critical insight into how to intervene in HIV stigma to increase HIV testing and improve HIV prevention among at-risk populations.
Keywords: Adolescent; Adult; Age Factors; Cross-Sectional Studies; Female; Health Behavior; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Middle Aged; Models, Theoretical; New England; Patient Acceptance of Health Care; Perception; Prejudice; Regression Analysis; Risk Reduction Behavior; Social Discrimination; Social Stigma; Socioeconomic Factors; Stereotyping; Young Adult